The practice of reporting Shariah non-compliant income in the annual financial report of Islamic commercial banks in Malaysia - Nabilah Mat Nor,; Mohd Fuad Md Sawari, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Bank Negara Malaysia (BNM) had introduced a policy document of Financial Reporting for Islamic Banking Institutions, which came into effect on 1st January 2018. This policy aimed to facilitate the assessment of Islamic financial institutions’ financial positions, performance, and Shariah compliance. However, the disclosure of Shariah committee report of a few Islamic banks may not have fulfilled the standard specified by BNM in terms of reporting the Shariah non-compliance incomes in their annual financial reports. This study therefore aims to investigate the extent of the application of BNM policy document for Islamic banks, with special focus on the practice of Islamic commercial banks in reporting Shariah non-compliant incomes in their annual financial reports. The qualitative method is adopted as the main research methodology of this study in order to gain information from the banks’ annual financial reports, as well as related research in the field. The findings show that nine out of sixteen Islamic commercial banks in Malaysia have fulfilled the standard provided by Bank Negara in reporting Shariah non-compliant incomes with complete detail in their annual financial reports. However, the remainder of the Islamic commercial banks did not properly disclose their Shariah non-compliant incomes in their report. This research would contribute to the practitioners of Islamic Commercial Banks in terms of providing transparent information with regards to business and financial dealings.